(untitled) (Scientific journal of the Fergana State University, 2023)
The optimal functioning of the state archival system largely depends on the creation of a legal framework for their activities. The article describes the process of forming the legal foundations of archiving in Uzbekistan in the years of independence. Today, this topic has not been specially studied in the historical and archival literature. A small book by Sh.A. Khayitov va A.Kh.Khamraev “Archival legislation of the Republic of Uzbekistan” (2008) has been published, but it is a collection of laws and regulations on archival affairs, in which these legislative acts are not subjected to scientific analysis. The main sources for writing this article were the laws of the Republic of Uzbekistan on archival affairs and the corresponding decrees of the government of the republic. Electronic resources and existing scientific literature were also involved. In preparing the article, such methodological techniques were used as a retrospective method, a systematic approach, problem-chronological and comparative analysis.It is concluded that in Uzbekistan during the years of independence, due to the creation of a legal framework, there have been many positive changes in the activities of archives.